1993
DOI: 10.1159/000182712
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density in Children and Adolescent Females Treated with High Doses of L·Thyroxine

Abstract: Single-photon absorptiometry was used to assess forearm bone mineral content (BMC) at a proximal site (PBMC) and at a more distal site (DBMC) of the non-dominant distal forearm in 20 children and adolescent females taking high doses of L-thyroxine (120 µg/m2/day) for a period of 6-96 months for endemic goiter, Hashimoto’s thyroiditis or thyroid cancer. PBMC was significantly reduced compared to controls (p < 0.002). No correlation was found between PBMC, the values of circulating thyroid hormones an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…Conflicting results have also been reported in children. A significant reduction in peripheral BMD has been found in children and adolescents receiving suppressive doses of L-T4 treatment for endemic goiter, Hashimoto's thyroiditis or thyroid cancer (10). However the majority of studies suggest that long-term L-T4 treatment in children and adolescents with CH (11), diffuse goiter (14) or with chronic lymphocytic thyroiditis (12) did not affect BMD nor had a negative effect on the attainment of peak bone mass.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conflicting results have also been reported in children. A significant reduction in peripheral BMD has been found in children and adolescents receiving suppressive doses of L-T4 treatment for endemic goiter, Hashimoto's thyroiditis or thyroid cancer (10). However the majority of studies suggest that long-term L-T4 treatment in children and adolescents with CH (11), diffuse goiter (14) or with chronic lymphocytic thyroiditis (12) did not affect BMD nor had a negative effect on the attainment of peak bone mass.…”
Section: Resultsmentioning
confidence: 99%
“…Thyroid hormones directly affect bone cells stimulating osteoclastic and osteoblastic activity, with a predominance of bone resorption during hyperthyroidism, resulting in a decreased bone mass (8,9). A significant reduction of peripheral bone mineral density (BMD) has been found in children and adolescents receiving L-T4 overtreatment for goiter, Hashimoto's thyroiditis or thyroid cancer (10), however other studies indicated that long-term L-T4 treatment does not seem to affect bone mineral metabolism and BMD in patients with thyroid diseases (11 -14). Congenital hypothyroidism (CH) is one of the most common thyroid diseases in children; early detection by neonatal screening has significantly improved mental and auxological outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Conflicting results were reported also in children. A significant reduction in peripheral BMD was found in children and adolescents receiving suppressive doses of L-T4 treatment for endemic goiter, Hashimoto's thyroiditis or thyroid cancer (Radetti et al, 1993). …”
Section: Thyroid Hormone Suppressive Therapymentioning
confidence: 99%
“…One cross-sectional study reported that radial bone mineral content of girls and adolescent females treated with high doses of L-T4 was significantly reduced [19]. Other authors [5] found in adult females that long-life treatment with L-T4 for congenital hypothyroidism led to a significant reduction of radial bone mineral content and BMD in comparison with controls.…”
Section: Monthsmentioning
confidence: 99%
“…The few data on bone mineral density (BMD) in L-T4 treated children and adolescents demonstrated a significant reduction in peripheral BMD in those receiving high doses [19]. There are no longitudinal studies to assess the impact of L-T4 treatment on BMD during adolescence.…”
Section: Introductionmentioning
confidence: 99%